2016
DOI: 10.1002/term.2200
|View full text |Cite
|
Sign up to set email alerts
|

Integrated culture platform based on a human platelet lysate supplement for the isolation and scalable manufacturing of umbilical cord matrix-derived mesenchymal stem/stromal cells

Abstract: Umbilical cord matrix (UCM)-derived mesenchymal stem/stromal cells (MSCs) are promising therapeutic candidates for regenerative medicine settings. UCM MSCs have advantages over adult cells as these can be obtained through a non-invasive harvesting procedure and display a higher proliferative capacity. However, the high cell doses required in the clinical setting make large-scale manufacturing of UCM MSCs mandatory. A commercially available human platelet lysate-based culture supplement (UltraGRO , AventaCell B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 53 publications
3
38
1
Order By: Relevance
“…Importantly, the process did not compromise UCM identity, since they maintained the typical MSC immunophenotype and multilineage differentiation potential . To our best knowledge, the expansion results obtained are comparable, or even superior, to those described in the literature for MSC obtained from UCM …”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Importantly, the process did not compromise UCM identity, since they maintained the typical MSC immunophenotype and multilineage differentiation potential . To our best knowledge, the expansion results obtained are comparable, or even superior, to those described in the literature for MSC obtained from UCM …”
Section: Discussionsupporting
confidence: 62%
“…To establish the expansion platform, we first adapted the culture conditions previously reported by our group for the expansion of UCM MSC in spinner flasks, using plastic microcarriers combined with hPL‐supplemented medium . The same culture conditions were translated to the VW‐PBS system, including the initial cell density, microcarrier type and concentration, coating solution, agitation protocol during cell adhesion and feeding regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Soure and co-workers studied the effect of PL on the expansion of mesenchymal stem cells (MSCs) derived from umbilical cord using plastic microcarriers under dynamic conditions. (de Soure et al, 2017) Their results demonstrated the advantages of the use of PL for the effective expansion of MSCs in a xenogeneic-free microcarrier-based system. In the present study, it is proposed the fabrication of MeLam microparticles with encapsulated PL to be used as microplatforms for cell adhesion and expansion.…”
Section: Resultsmentioning
confidence: 83%